Analysis of dispensation of opioids in Brazil: 2014-2018 (Research, Society and Development, 2022)
The aim of this study was to describe the opioid dispensing profile in Brazil between 2014 and 2018. Data were collected on the number and type of opioid dispensed after professional prescription, between January 2014 and December 2018, from the National Controlled Products Management System (SNGPC), managed by the National Health Surveillance Agency (ANVISA), having as object of study the analysis of the variables: (1) Active Principle; (2) Quantity dispensed by state and (3) Origin of Professional Registration. A total of 60.675.488 drugs were marketed, with codeine phosphate being the most widely dispensed active ingredient, followed by tramadol hydrochloride, which together accounted for 95.9% (2014), 96.6% (2015), 96.2% (2016), 95.4% (2017) and 95.7% (2018). In practically every year, the average of medicines sold remained above 5,000 units per 100,000 inhabitants. São Paulo was the state that most commercialized opioids, and regarding the origin of the prescriber's professional record, doctors accounted for 93.2% of the medication dispensed. It was concluded that codeine phosphate was the most prescribed among the opioids dispensed. There was no trend towards an increase in dispensing in the period evaluated.